Approaches to the treatment of bacterial vaginosis - D.M. Ibragimova; Yu.E. Dobrokhotova (LCC «Medicine-Inform», 2018)
Approaches to the treatment of bacterial vaginosis D.M. Ibragimova, Yu.E. Dobrokhotova Pirogov Russian National Research Medical University, Moscow, Russian Federation Bacterial vaginosis (BV) is a clinical non-inflammatory syndrome that occurs in vaginal biotope dysbiosis and is accompanied by the replacement of lactic acid bacteria with a high concentration of an obligate and facultative anaerobic opportunistic microorganisms. BV is the most common cause of abnormal vaginal discharge in women of childbearing age and is observed in patients with high sexual activity. Studies have shown that in BV, polymicrobial biofilm forms due to which a microflora forming it becomes more resistant to the effects of adverse events of various nature, including due to the formation immediately after adhesion of the mucous-polymer layer. At present, there are European and American Guidelines for the treatment of patients with BV, but a single generally accepted approach has not yet been developed. Therefore, treatment should be individualized based on a comparison of effectiveness, convenience, potential adverse events, and cost. An application of local drugs is pathogenetically justified since they are the safest, highly effective, have a wide spectrum of action and are not inclined to form the resistance. Of practical interest is the drug METROMICON-NEO® in the form of vaginal suppositories. The drug is a combination of metronidazole and miconazole, due to which it has antibacterial, antiprotozoal and antifungal effects. Key words: bacterial vaginosis, bacteria, Lactobacillus, metronidazole, miconazole, METROMICON-NEO. For citation: Ibragimova D.M., Dobrokhotova Yu.E. Approaches to the treatment of bacterial vaginosis. Russian Journal of Woman and Child Health. 2018;1(2):174-177.